The Effect of Fraud Hexagon on Academic Fraud with Patriotism Attitude as a Moderating Variable - Ferdy Septiansyah Wardhana; Gideon Setyo Budiwitjaksono (Balance Vocation Accounting Journal, 2026)
Academic cheating has become a common phenomenon in the world of education. This study aims to examine the influence of the dimensions of the fraud hexagon (pressure, opportunity, rationalization, capability, ego, and collusion) on academic cheating, with patriotic attitude as a moderating variable. This study uses a quantitative method with a sample of 314 accounting students at the Veteran National Development University in East Java. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The results showed that the variables of opportunity, capability, and collusion had a positive and significant effect on academic fraud. Conversely, pressure, rationalization, and ego were found to have no significant effect. Patriotism as a moderating variable only weakened the effect of pressure on academic cheating, but did not moderate the effects of other variables. These findings indicate that even though students have a sense of patriotism, their intentions and internal motivations to cheat are often more dominant.